10.1016/s0029-7437(07)70777-2 (CrossRef Listing of Deleted DOIs, 2000)
AIMS: Etrasimod is an oral sphingosine-1-phosphate receptor modulator approved for moderate-to-severe ulcerative colitis. The impact of CYP2C9 polymorphisms and hepatic impairment on etrasimod exposure remains unclear. This study aimed to characterize their effects and identify clinically relevant dose adjustment strategies in Chinese patients. METHODS: A physiologically based pharmacokinetic model was developed and verified using in vitro metabolism and single-dose, multiple-dose and drug-drug interaction clinical pharmacokinetic data. The validated model was extrapolated to Chinese populations with different CYP2C9 genotypes and hepatic impairment severity to characterize exposure changes and optimize dosing. RESULTS: Most predicted pharmacokinetic parameters are within a twofold error range. At the approved dose of 2 mg once daily, the predicted median steady-state AUC0-24 and Cmax were 1976.95 ng·h/mL (95% prediction interval [PI]: 975.78-4144.29 ng·h/mL) and 98.40 ng/mL (95% PI: 52.9-190.51 ng/mL) in Caucasian subjects and 1988.82 ng·h/mL (95% PI: 814.91-4244.10 ng·h/mL) and 105.18 ng/mL (95% PI: 51.30-198.03 ng/mL) in Chinese subjects, respectively. In Chinese populations, hepatic impairment and CYP2C9 polymorphisms increased etrasimod exposure, with the greatest increase observed in CYP2C9 poor metabolizers with Child-Pugh C hepatic impairment (67% increase in AUCss). CONCLUSIONS: CYP2C9 polymorphisms and hepatic impairment increased etrasimod exposure, particularly when combined. Model-based exposure matching supported dose reduction to 1.5 mg once daily for most affected subgroups and to 1 mg once daily for CYP2C9 poor metabolizers with Child-Pugh C hepatic impairment, providing quantitative support for individualized dosing.